Preventive effect of purgative manna on neonatal jaundice: A double blind randomized controlled clinical trial. (23rd May 2019) - Fakhri, Moloud; Farhadi, Roya; Mousavinasab, Nouraldin; Hosseinimehr, Seyed Jalal; Yousefi, Seyede Seddigheh; Davoodi, Ali; Azadbakht, Mohammad
Abstract: Ethnopharmacological relevance: Cotoneaster nummularioides Pojark manna (Shir-e-Khesht) is popular in Persian medicine. Different effects of some Cotoneaster species manna include antibacterial, antioxidant, anticancer, and hepatoprotective effects, as well as bilirubin serum levels reduction. Cotoneaster species manna is used in many parts of Iran as a laxative and accelerates the passage of meconium. Neonatal jaundice has relatively costly and sometimes invasive therapeutic interventions, which its prevention from becoming severe cases can be a priority in neonatal medicine. Aim of the study: The aim of this study was to evaluate the effectiveness of an herbal product ( Purgative Manna, native to Iran and Asian countries) in preventing severe cases of jaundice and reducing total bilirubin levels in neonates. Materials and methods: This randomized double-blind controlled clinical trial included full-term babies. Four hundred and forty-five (445) eligible neonates were assigned to two groups using the block balanced randomization method; 222 neonates received the Purgative Manna product as drops, and 223 neonates received placebo drops. The neonates received a dose of 5 drops per kilogram of neonatal weight (divided into three doses per day) for three days. The treatment period was three days, and a 24-h (three times) examination was performed to measure the initial outcome of the trial (i.e., the total serum bilirubin level). The secondary outcomes of this trial were the need for hospitalization due to jaundice and/or phototherapy from 4 to 14 days after birth, the frequency of defecation within 24 h, and the triple complications of diarrhoea, dehydration symptoms, and abdominal colic. Results: In this study, 220 neonates in the Purgative Manna product group and 222 neonates in the placebo group completed their interventions within the predicted period of the study. At the end of study, the total bilirubin level in the Purgative Manna treated group was significantly lower than that of the placebo group. The difference between the mean total bilirubin levels of the two groups was approximately 2.1 mg/dl on the third day after treatment, with an effect size of 0.79 (95% CI: 0.06–0.98). The relative risk for reducing the need for hospitalization or phototherapy in the group treated with Purgative Manna drops was 0.26, compared with the placebo group. The risk of occurrence of severe jaundice or phototherapy in the Purgative Manna group was 75% lower than that of the placebo group. The median frequency of defecation in the intervention group at three time intervals in the first, second and third days after treatment was 1–2 times more than that of the comparison group (p < 0.001). Conclusions: Meanwhile, considering the fact that one in every eight neonates who used the product avoided having a severe and high-risk case of jaundice or the need for phototherapy intervention (even through an exchange transfusion), the use of Purgative Manna drops can be recommended; however, further study is necessary. Graphical abstract: Image 1